The Effects of Synbiotics and Probiotics Supplementation on Growth Performance of Red Hybrid Tilapia, Oreochromis mossambicus x Oreochromis niloticus - Jahari, Muhamad Amin; Mustafa, Shuhaimi; Roslan, Muhamad Akhmal Hakim; Manap, Yazid Abd; Lamasudin, Dhilia Udie; Jamaludin, Farahiyah Ilyana (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
The purpose of this study was to evaluate the influence of a synbiotics between Lactobacillus plantarum and mannan-oligosaccharides (MOS) extract and probiotics (Lactobacillus plantarum) on growth performance in red hybrid tilapia (Oreochromis mossambicus x Oreochromis.niloticus). The fishes with initial average weight 11.9 Â± 0.7g were randomly assigned to three dietary treatments which were fed on a diet containing probiotics only and a diet combination of probiotics and prebiotic (synbiotics), with four replicates for each treatment. The control group was fed without supplementation of any probiotics or prebiotics for the same duration. All the diets were isocaloric and isonitrogenous. All fish were fed daily at 3% of the body weight per day in two equal instalments. The feeding rate was kept at 4% body weight day-1 for the whole rearing period of 30 days, and the amount of feed was adjusted every tenth day following a bulk weighing of each group of fish. All diets contained about 32% of crude protein. Significantly (P < 0.05) high growth performance (percent gain body weight, weight gain and feed intake) were observed in the group fed diet containing synbiotics as compared to probiotics and control group. Similarly, significantly (P < 0.05) low FCR was recorded in synbiotics as compared to probiotics and control group. This result revealed that a feeding regime with synbiotics for 30 days led to a significant increase in growth performance, survival rate and feeding efficiency in red hybrid tilapia fingerlings.